تأثير أسلوب الغناء لتنمية فهم علم الالات لدى طلاب الفصل الثاني بمعهد دار الحكمة الإسلامي فراسوغ بودوران سيدوارجو - Nahdly, M. Asad; Al Mubaro, Muhammad Zamzain (Al-Muttaqin : Jurnal Studi, Sosial, dan Ekonomi, 2022)
arul Hikmah Islmaic Boarding School in which the Arabic language becomes the language of communication for students because of what has been mentioned that needs to understand machine science, and teachers have fallen into difficulties in making this, because the song is one of the methods that the researcher chooses to develop understanding. Using the song makes it easier for students to understand. Singing is a style. The style is a set of rules or controls used in teaching methods to achieve the goals of teaching. As it is known that life has a goal, and every action has a goal. The general purpose of the research is: 1) To know the effect of the singing style for developing the understanding of instrumental science among students of the second semester at the Darul Hikmah Islmaic Boarding School, Prasung, Buduran Sidoarjo. 2) To find out the effect of the singing style on developing the understanding of instrumental science among students of the second semester at the Darul Hikmah Islmaic Boarding School. As for the approach to this research, it is the quantitative approach, and the type of research is experimental research. And the entrance to this research is a quantitative approach and the use of quantitative analysis, which assumes that the observed phenomena It is measured in numerical form. The method of collecting data that the researcher is conducting is the method of testing and observation. Based on the result of the effect of the singing style to develop the understanding of instrumental science among students of the second semester at the Darul Hikmah Islmaic Boarding School, Prasung Buduran Sidoarjo. The presence of the relationship and the influence on the students is: We know from the researcher's t-test result. The researcher knew that the statistic t of 10 is greater than the tabular t, the moral level 1% means 2.80, and also greater than the moral level 5% 2.06. Thus, he knows that Ha is acceptable and Ho is rejected. Therefore, the use of singing style has a relationship and impact in developing the understanding of instrumental science among second-year students at Darul Hikmah Islmaic Boarding School